Pengaruh Kombinasi Pupuk Hara Mikro Cair Dengan N,P,K terhadap Kadar Cobalt dan Hasil Tanaman Jagung (Zea mays L.) ‘Pioneer 12‘ pada Fluventic Eutrudepts - Dilla Amelia; E Hidayat Salim; Oviyanti Mulyani (Soilrens, 2017)
The content of trace elements in the soil and plant is generally very low. Cobalt (Co) is a trace element that has an important role for plant metabolism. This research was conducted to study the combination effect of liquid micro fertilizer (LMF) with N,P,K fertilizer on total Co, available Co, Co uptake and corn yield (Zea mays L.)  var. Pioneer 12 on Fluventic Eutrudepts. This research was conducted at the test field of Soil and Water Management, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor. The altitude located at ± 725 meters above the sea levels. This research held from January to May 2014. The experimental design used were Randomized Design Group with ten treatments and three replications, with the total of experimental plots were 30 plots. The treatments consisted of control (without fertilizer) and combination of dosage LMF (0, ½, 1, 1½, and 2) with N, P, K fertilizer (0, ¼, ½, ¾, and 1). The results showed that the combination application of LMF + N, P, K significantly affect the Co uptake and corn Pioneer 12 yield. Combination effect of LMF (1, 1½, and 2) with 1 dosage of N,P,K fertilizer gave the best results of 19.93, 18.57,and 18.17 kgs plot-1 or equivalent with 8.47, 7.89, and 7.72 tons ha-1 respectively. Keywords: corn, cobalt, Fluventic Eutrudepts, micro fertilizer